Resting state effective connectivity between inferior parietal lobe (IPL) and inferior temporal gyrus (ITG) in the left and right hemispheres - Ahmad Nazlim Yusoff,; Khairiah Abdul Hamid,; Saemah Rahman,; Syazarina Sharis Osman,; Shahlan Surat,; Maziah Ahmad Marzuki, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Inferior parietal lobule (IPL) and inferior temporal gyrus (ITG) are two important brain regions for the default mode network (DMN). IPL has been known to be involved in the control of attention and responding to given information while ITG is involved in the processing and perception awakened by visual stimuli. These two key DMN regions are highly interconnected as determined from white matter and fiber tracking studies. However, little is known about their nature of connectivity while the brain is at rest, whether it is linear, bilinear or nonlinear and whether it is of mono- or bi-direction. Resting state functional magnetic resonance imaging (rsfMRI) data were obtained from 7 healthy male and female participants (average age = 20.7 ± 4.5 years) and were concatenated. Data were analyzed using statistical parametric mapping (SPM12). Endogenous brain signals were modelled by Fourier series at 0.01 – 0.08 Hz. IPL-ITG connected linear, bilinear and non-linear causal models in both hemispheres were constructed and estimated by means of stochastic dynamic causal modelling (sDCM) and were compared using Bayesian Model Selection (BMS) for group studies. Group fixed-effects results indicated that bilateral IPL and ITG exhibited high neural activity at a corrected significant level (pFWE < 0.05). Neural activity was centered in ITG (-32/2/-38) in the left hemisphere but shifted to IPL (32/-38/50) in the right hemisphere indicating different control center for both hemispheres. BMS selected bilinear model as the optimal model for both hemispheres (model posterior probability ~ 1.0; log evidence > 1000) which has the best balance between model accuracy and difficulty. The minimum free energy (F) = -4.41 × 104 and -4.09 × 104 for left and right hemisphere bilinear models respectively. From BMS and DCM results, it was found that IPL and ITG do have a dynamic collaboration between each other, a connectivity that belongs to a greater network when the brain is at rest. The intrinsic connections between them are negative in both directions i.e. IPL and ITG mutually inhibited each other. The effective connectivity was modulated by the endogenous fluctuation of the brain signal.